Mechanism and structural diversity of exoribonuclease-resistant RNA structures in flaviviral RNAs - Andrea MacFadden (Nature Portfolio, 2018)
Subgenomic flavivirus RNAs are generated by a host exoribonuclease and play an important role in virus replication and pathogenesis. Here, the authors show the mechanism by which subgenomic flavivirus RNAs are generated and identify two structurally distinct sfRNA classes in flaviviruses.